2018
DOI: 10.1021/acsnano.8b06026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Hyperbolic Metamaterial Assisted Illumination Nanoscopy

Abstract: An optical metamaterial is capable of manipulating light in nanometer scale that goes beyond what is possible with conventional materials. Taking advantage of this special property, metamaterial-assisted illumination nanoscopy (MAIN) possesses tremendous potential to extend the resolution far beyond conventional structured illumination microscopy. Among the available MAIN designs, hyperstructured illumination that utilizes strong dispersion of a hyperbolic metamaterial (HMM) is one of the most promising and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The large‐wavevector evanescent waves could be provided by a high‐refractive‐index waveguide or HMMs without wavevector cutoff. [ 50,138,286,287 ] Various researches have been done to continuously tune the wavevector. For dielectric waveguides, one direct way is to adapt the wavevector of evanescent waves by varying the wavelength of the incident light.…”
Section: Superresolution Imaging Based On Sfs Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large‐wavevector evanescent waves could be provided by a high‐refractive‐index waveguide or HMMs without wavevector cutoff. [ 50,138,286,287 ] Various researches have been done to continuously tune the wavevector. For dielectric waveguides, one direct way is to adapt the wavevector of evanescent waves by varying the wavelength of the incident light.…”
Section: Superresolution Imaging Based On Sfs Methodsmentioning
confidence: 99%
“…In 2018, Ma et al [138] experimentally demonstrated the hyperstructured illumination by using an Ag/SiO 2 multilayer HMM. With a pair of nanoslits as a point source on HMM, the HMM can perform a 1D mapping from spatial locations in a subdiffraction scale to a spectrum.…”
Section: Sfc Through Hyperlensmentioning
confidence: 99%
“…The characteristic of HMM to support sub-diffractionlimited optical patterns has recently been exploited to improve the resolution of conventional microscopy by combining HMMs with conventional structured illumination microscopy [88][89][90]. HMMs are used to generate sub-diffraction-limited structured light patterns, and the scattering fields are collected in the far-field to improve spatial resolution down to ∼ 40 nm [90].…”
Section: High-resolution Optical Imaging and Nanoscale Lithographymentioning
confidence: 99%
“…Due to the evanescent nature of localized surface plasmons, LPSIM is best applied to image very thin objects or at the surface of a thick object. An alternative is to use a hyperbolic metamaterial assisted illumination which uses a metallic/dielectric alternating layered structure to achieve super-resolution imaging at the far-field [110]. A resolution of 80 nm which is sixfold resolution enhancement of the diffraction limit has been achieved with an Ag/SiO 2 multilayer structure.…”
Section: Super-resolution Imagingmentioning
confidence: 99%